The usage of direct and indirect learning strategies fostering interactions in group discussions / Angelina Subrayan...[et al.] - Subrayan, Angelina; Thevarajoo, T Parimala Devi; Ahmad Buhari, Turisiana (Universiti Teknologi MARA, Kedah, 2020)
The 4IR has influenced learners in many ways and one of them is the ability to learn collectively and from each other. A large number of students have resorted to learning individually without considering the benefits of studying in groups. The purpose of this study was to examine learners’ usage of direct and indirect learning strategies when they interacted in group discussions. It added to the present degree of knowledge and understandings pertaining to the principle behind an effective group work and learning strategies in higher institutions and is centred on students’ involvements in group work that included acquiring knowledge in groups. The participants for this study comprised of students from selected English proficiency courses. They responded to a survey, and the data from the survey was then analysed using the SPSS. The result shows that students were able to develop knowledge on various content-based topics and they have also learnt to interact and improve their social skills using direct and indirect learning strategies in group work activities. The activities in the ESL classrooms incorporated group work for maximum group and social interaction. The findings for this study show positive implications for group interactions in the ESL classrooms